Effect of two-step microwave heating on the gelation properties of golden threadfin bream (Nemipterus virgatus) myosin. (30th October 2020) - Li, Zhiyu; Sun, Qian; Zheng, Yimei; Wang, Jianyi; Tian, Yuting; Zheng, Baodong; Guo, Zebin
Highlights: Mild microwave heating increased myosin solubility with suitable conformation. 100 W coupled with 300 W microwave could obviously improve gelation properties. Two-step microwave heating contributed to a compact three-dimensional network. Two-step microwave heating enhanced protein-water hydrogen bonds during gelling. Abstract: The effects of different microwave heating (MH) methods on gelation properties of golden threadfin bream myosin and related mechanism were investigated in this study. Compared with conventional heating and one-step MH methods, myosin gel developed by 100 W coupled with 300 W MH method (MH100 + MH300) had stronger gel strength ( p  < 0.05) with more immobilized water ( p  < 0.05). Raman analysis suggested that this two-step method promoted the suitable unfolding of myosin before aggregation formation, and contributed to stabilizing the ordered secondary structure. Confocal laser scanning microscopy images revealed that 100 W microwave followed by 300 W MH produced a compact networked structure with small cavities and a thick cross-linked gel wall. Furthermore, from a perspective of molecular forces, the improvement of gelation properties by the MH100 + MH300 method were mainly involved in the enhancement of regular hydrophobic interaction and stabilization of weak protein-water hydrogen bonds.